Peuz-Jeghers syndrome. New therapeutic approach endoscopic-surgical - Barberousse, Carlos; Kierszembaun, Carlos; Trucco, Elena; Carriquiry, Luis (Cirugía del Uruguay, 2000)
The Peutz-Jeghers Syndrome is a very inrequent hereditary disorder. The main characteristic is the association of intestinal polyps and pigmented spots on lips and bucea! mucous. lts natural history is about recurrent attacks of co!icky abdominal pain due to episodes of intestinal invagination. This results in mu/tiple and acute laparotomies with considerable morbidity and mortality which final/y develop in a short bowel syndrome. Recent studies have a/so determínate a greater incidence of intestinal and extraintestinal cancer in this patients.